2015
DOI: 10.1177/0840470415581244
|View full text |Cite
|
Sign up to set email alerts
|

Access to psychiatrists by French-speaking patients in Ontario hospitals

Abstract: There has been a limited amount of research suggesting that cultural and linguistic variables may affect access to health services, but no study has examined the access of French-speaking Canadians to psychiatrists. The present study used data from the Ontario Mental Health Reporting System to examine patterns of daily contact with psychiatrists in the first 3 days of admission to mental health facilities in Ontario. The results showed that after controlling for a broad range of covariates, French-speaking Ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
1
4
0
4
Order By: Relevance
“…23 The finding of markedly longer LOS among French-speaking patients in psychiatric hospitals bears further analysis, although it aligns with previous research, which found that French-speaking patients were about one-third as likely to have daily contact with a psychiatrist in the first 3 days of admission. 24 The associations observed between psychosocial factors, LOS, and GAF improvement are consistent with other research on psychosocial determinants, suggesting better trajectories among individuals with greater social support (e.g., married) and better engagement with education and employment. 25,26 As proxy indicators of acuity, with implications for the adequacy of supports postdischarge, 27 the number of previous hospitalisations and recency of prior discharge suggest a pattern of individuals with more hospitalisations and more difficult community transitions having long LOS and making fewer gains.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…23 The finding of markedly longer LOS among French-speaking patients in psychiatric hospitals bears further analysis, although it aligns with previous research, which found that French-speaking patients were about one-third as likely to have daily contact with a psychiatrist in the first 3 days of admission. 24 The associations observed between psychosocial factors, LOS, and GAF improvement are consistent with other research on psychosocial determinants, suggesting better trajectories among individuals with greater social support (e.g., married) and better engagement with education and employment. 25,26 As proxy indicators of acuity, with implications for the adequacy of supports postdischarge, 27 the number of previous hospitalisations and recency of prior discharge suggest a pattern of individuals with more hospitalisations and more difficult community transitions having long LOS and making fewer gains.…”
Section: Discussionsupporting
confidence: 87%
“…23 The finding of markedly longer LOS among French-speaking patients in psychiatric hospitals bears further analysis, although it aligns with previous research, which found that French-speaking patients were about one-third as likely to have daily contact with a psychiatrist in the first 3 days of admission. 24…”
Section: Discussionmentioning
confidence: 99%
“…The 65 years and older population is one that presents more complex needs, increasing the importance of improving service access for them. Difficulties in access to linguistically appropriate services has been reported for a different population (Tempier et al 2015), in other Canadian provinces (Carter 2012;De Moissac et al 2015;De Moissac and Bowen 2017;Forgues and Landry 2014) and other countries with two official languages such as Wales in the UK (Madoc-Jones 2004;Martin et al 2018;Roberts and Burton 2013) or Finland (Eriksson-Backa 2008). The proposed framework could be used in future studies for national or international comparison of access to and continuity of health and social services for OLMCs.…”
Section: Study Limitationsmentioning
confidence: 99%
“…La barrière linguistique dans l'accès aux services de santé mentale (Traisnel et Forgues, 2009) est un véritable poids pour les francophones en situation minoritaire au Canada. En utilisant les données de l'Ontario Mental Health Reporting System, une étude récente (Tempier, Bouattane et Hirdes, 2015) montre que la langue constitue une barrière importante pour les francophones de cette province dans le recours aux services spécialisés de santé mentale. D'autres données (Vaillancourt et Lacaze-Masmonteil, 2009) ont cependant mis en exergue que même lorsque des services de santé mentale en français sont disponibles en contexte minoritaire, ils ne sont pas toujours utilisés par la population visée.…”
Section: Les Barrières D'accès Aux Services De Santé Mentaleunclassified